Effectiveness of traffic light system on Brazilian consumers perception of food healthfulness - Mayara Lima; Marcela de Alcantara; Amauri Rosenthal; Rosires Deliza (Food Science and Human Wellness, 2019)
Front-of-package (FOP) nutrition labelling schemes were developed to improve consumer’s comprehension about the food nutrients associated with non-communicable diseases (NCDs). Several FOPs have already been developed, and Brazil is in the process of evaluating a scheme to introduce in the products. The aim of this study was to investigate the impact of TLS, the scheme proposed by the food industry, on the product healthfulness perception. A study with 141 participants was carried out. A conjoint task was designed considering three categories and levels: types of dairy products (light yogurt, prato cheese, and chocolate flavoured milk), Traffic Light System (yes vs. no) and brand (well-known vs. unknown). The effect of TLS on perceived healthfulness was evaluated using a 9-point scales (1: not healthy; 9: very healthy). Results showed that the inclusion of TLS did not influence the perceived healthfulness of the products by consumers, even among consumers with higher interest in healthy eating. These findings suggest that the proposal supported by the food industry does not seem to be the most appropriate, being recommended the development of further studies to compare the efficacy of TLS and other FOP schemes. Keywords: Front of pack, Traffic light system, Healthfulness perception, Food products